2014
DOI: 10.1111/jtxs.12079
|View full text |Cite
|
Sign up to set email alerts
|

Rheological and Thermal Behavior of Mixed Gelatin/Konjac Glucomannan Gels

Abstract: Mixed konjac glucomannan/gelatin gels were mechanically characterized in the linear and large deformation regimes. Differential scanning calorimetry revealed no effect of konjac addition on gelling and melting of gelatin. The elastic moduli increased with increasing konjac content, but fracture stress slightly decreased. The rheological results and confocal laser scanning microscopy support segregative phase separation, where rigid polysaccharide domains act as bound fillers which are not separated by the solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 39 publications
(59 reference statements)
0
15
0
Order By: Relevance
“…The higher correlation of the sensory attribute with the logarithm of the physical property (compared with correlation with the physical quantity itself) is a manifestation of the Weber–Fechner law (Sone, ). We will look at the correlation of the sensory hardness, as reported by Tomczyńska‐Mleko et al (), with large‐deformation stress parameters from extrusion and uniaxial compression performed at 22C and large‐amplitude oscillatory shear performed at 25C. The parameters are the maximum extrusion pressure (tapering ratio 8.5, flow rate 2 ml/s), the engineering compression stress at 90% compression, σ 90, and the fracture stress in oscillatory shear, τ f .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The higher correlation of the sensory attribute with the logarithm of the physical property (compared with correlation with the physical quantity itself) is a manifestation of the Weber–Fechner law (Sone, ). We will look at the correlation of the sensory hardness, as reported by Tomczyńska‐Mleko et al (), with large‐deformation stress parameters from extrusion and uniaxial compression performed at 22C and large‐amplitude oscillatory shear performed at 25C. The parameters are the maximum extrusion pressure (tapering ratio 8.5, flow rate 2 ml/s), the engineering compression stress at 90% compression, σ 90, and the fracture stress in oscillatory shear, τ f .…”
Section: Resultsmentioning
confidence: 99%
“…While several sensory attributes were evaluated, we will refer only to the hardness, defined as the perceived force needed to bite completely through the sample with incisors or molars. The results of sensory evaluation of the GLT/KGM gels were reported in our earlier study (Tomczyńska‐Mleko et al, ) and are tested in our current report against extrusion test results that were not reported previously, as well as against other mechanical test results that were included in the original study.…”
Section: Methodsmentioning
confidence: 95%
See 2 more Smart Citations
“…Tomczyńska‐Mleko et al . () studied the texture of mixed gels of gelatin, KGM and LBG, and found that the addition of KGM and LBG made gelatin gels softer but the excessive addition made the gel too sticky. They obtained a gel from 5% gelatin, 1% KGM and 0.5% LBG which was the easiest for mastication and swallowing among other combinations…”
Section: Optimising Texture Properties For Safe Swallowingmentioning
confidence: 99%